2015
DOI: 10.1016/j.freeradbiomed.2015.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of oxygen dependence on in vitro and in vivo cytotoxicity of photoimmunotherapy using IR-700–antibody conjugates

Abstract: Photoimmunotherapy (PIT) using the near infrared-absorbing photosensitizing phthalocyanine dye, IRDye 700DX (IR700) conjugated with a tumor-targeting antibody such as Panitumumab (Pan) has shown efficacy in vitro studies and several pre-clinical models in mice with promise for clinical translation. PIT results in rapid necrotic cell death in vitro and tumor shrinkage in vivo. Photochemical studies with the Pan-IR700 conjugate showed that this agent can support generation of singlet oxygen and also generate rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…5,12 Unlike conventional plasma membrane-targeted photosensitizers, an mAb-IR700 is sufficiently far away from the plasma membrane and does not induce oxidative damage because of the very short half-life of singlet oxygen. 12,34 There is a report that free radical scavengers reduced the effect of NIR-PIT, 35 although this has not been generally accepted. 5,11 The molecular mechanism causing such minute plasma membrane damage in NIR-PIT remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 Unlike conventional plasma membrane-targeted photosensitizers, an mAb-IR700 is sufficiently far away from the plasma membrane and does not induce oxidative damage because of the very short half-life of singlet oxygen. 12,34 There is a report that free radical scavengers reduced the effect of NIR-PIT, 35 although this has not been generally accepted. 5,11 The molecular mechanism causing such minute plasma membrane damage in NIR-PIT remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…BT142 seemed to have the characteristics of apoptosis and necrosis within 60 m.[21,22] It is consistent with the reported result that photodamage of A431-cells by IR700 induced both apoptosis and necrosis. [23] At 2 h after photoactivation, vesicles in BT142 cells diffused in the same degree as U87MG cells and the fragmentation of the nucleus detected by EthD-1 was not observed, suggesting necrotic cell death. These results indicate that BT142 had characteristics of necrotic and apoptotic cell death in an early stage of cell damage and progressed in necrotic cell death at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…Photoactivation of IR700 was recently developed to specifically damage cancer cells in vitro and in vivo (Harada et al, 2015; Nagaya et al, 2016). Previous research has shown that photoactivation induces cellular damage by producing ROS and heat (Mitsunaga et al, 2011; Kishimoto et al, 2015). To specify the effect of photoactivation, we applied a motility assay of kinesin and dynein to microtubules (Fig.…”
Section: Discussionmentioning
confidence: 99%